Epoxy adhesive capable of being rapidly cured at low temperature as well as preparation method and application of epoxy adhesive

Through the combination technology of epoxy resin composition and modified particles, the problem of slow curing speed of traditional epoxy adhesives under low temperature conditions is solved, and rapid curing at low temperature is achieved and excellent waterproof, mechanical and aging resistance is maintained. Meet diversified application needs.

CN119193070AInactive Publication Date: 2024-12-27BONDWAY (DONGGUAN) ELECTRONIC MATERIALS TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411251830.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional epoxy adhesives cure slowly under low temperature conditions, affecting production efficiency, and may sacrifice properties such as waterproofness, mechanical and mechanical properties, and aging corrosion resistance during accelerated curing.

Method used

Using specific ratios of epoxy resin composition, modified particles, accelerator, curing agent, toughening agent, active diluent and stabilizer, the preparation method of compound and modified particles is used to form a diverse intermolecular action force. With complex multi-segment tangle phenomenon, improves curing efficiency and maintains excellent waterproof, aging resistance and mechanical properties.

Benefits of technology

It realizes fast curing of epoxy adhesives at low temperatures, maintains excellent adhesion and performance, meets diverse application needs, and has excellent application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005032662350000171
    Figure BDA0005032662350000171
  • Figure BDA0005032662350000181
    Figure BDA0005032662350000181
Patent Text Reader

Abstract

The invention relates to the field of adhesives, in particular to a low-temperature fast-curing epoxy adhesive as well as a preparation method and application thereof. The low-temperature fast-curing epoxy adhesive comprises the following raw materials in parts by mass: 60-90 parts of an epoxy resin composition, 15-25 parts of modified particles, 3-5 parts of an accelerant, 20-30 parts of a curing agent, 10-20 parts of a toughening agent, 15-30 parts of a reactive diluent, 1-2.5 parts of a stabilizer and 4-12 parts of a dispersing agent. The epoxy adhesive prepared by the invention not only has excellent adhesion and low-temperature curing effect, but also can maintain excellent water resistance, mechanical property, aging corrosion resistance and the like on the basis, thereby meeting the performance requirements of existing science and technology products on the diversity of epoxy adhesives, and having excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of adhesives, and in particular to a low-temperature fast-curing epoxy adhesive and a preparation method and application thereof. Background Art

[0002] Low temperature curing epoxy adhesives are adhesives that cure at relatively low temperatures and are often used for materials or applications that cannot withstand high temperature processing. These adhesives are widely used in many fields such as electronic packaging, automotive manufacturing, aerospace, and composite materials.

[0003] With the development of science and technology, there is an increasing demand for epoxy resin adhesives that can cure at low temperatures while maintaining good performance. This is mainly because many modern materials and components (such as electronic components) are heat sensitive and high temperature curing may cause them to be damaged. At the same time, epoxy resins are widely used due to their excellent adhesion, chemical stability, mechanical properties and electrical insulation properties.

[0004] The curing speed of traditional epoxy adhesives slows down significantly under low temperature conditions, affecting production efficiency, which has led researchers to focus on developing new curing systems or adding curing accelerators to solve the above problems. However, although such methods can further accelerate the curing efficiency under low temperature conditions, this may sacrifice certain properties of the final product, such as waterproofness, mechanical properties, aging and corrosion resistance, etc., which in turn restricts the application of epoxy adhesives.

[0005] Therefore, in order to solve the above problems, the present application provides a low-temperature fast-curing epoxy adhesive and a preparation method thereof. The epoxy adhesive prepared in the present application not only has excellent adhesion and low-temperature curing effect, but also can maintain excellent waterproofness, mechanical properties, aging corrosion resistance and other properties on this basis, thereby meeting the diverse performance requirements of existing scientific and technological products for epoxy adhesives, and has excellent application prospects. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides a low-temperature, fast-curing epoxy adhesive, which comprises, by mass, 60 to 90 parts of an epoxy resin composition, 15 to 25 parts of modified particles, 3 to 5 parts of an accelerator, 20 to 30 parts of a curing agent, 10 to 20 parts of a toughening agent, 15 to 30 parts of an active diluent, 1 to 2.5 parts of a stabilizer, and 4 to 12 parts of a dispersant.

[0007] As a preferred solution, the mass ratio of the epoxy resin composition, the modified particles and the dispersant is (70-85): (16-22): (6-10).

[0008] As a preferred solution, the mass ratio of the epoxy resin composition, the modified particles and the dispersant is (75-80): (17-20): (8-9).

[0009] As a preferred solution, the mass ratio of the epoxy resin composition, the curing agent and the toughening agent is (70-85): (20-25): (12-18).

[0010] As a preferred solution, the mass ratio of the epoxy resin composition, the curing agent and the toughening agent is (75-80): (20-24): (13-15).

[0011] As a preferred solution, the epoxy resin composition is a composition of bisphenol A epoxy resin, brominated epoxy resin and phenolic modified epoxy resin.

[0012] As a preferred solution, the mass ratio of the bisphenol A epoxy resin, the brominated epoxy resin and the phenolic modified epoxy resin is (4-6): (0.5-1.5): (1.5-2.5).

[0013] As a preferred solution, the mass ratio of the bisphenol A epoxy resin, the brominated epoxy resin and the phenolic modified epoxy resin is (5-5.5): (0.8-1): (1.5-1.8).

[0014] As a preferred solution, the epoxy equivalent of the bisphenol A epoxy resin is 200 to 300 g / eq.

[0015] As a preferred solution, the epoxy equivalent of the bisphenol A epoxy resin is 220 to 240 g / eq.

[0016] As a preferred solution, the number average molecular weight of the brominated epoxy resin is 1500 to 3000 Da.

[0017] As a preferred solution, the number average molecular weight of the brominated epoxy resin is 1400 to 2000 Da.

[0018] As a preferred solution, the bromine content of the brominated epoxy resin is 45 to 55 wt %.

[0019] As a preferred solution, the softening point of the brominated epoxy resin is 95-115°C.

[0020] As a preferred solution, the epoxy equivalent of the phenolic modified epoxy resin is 500 to 650 g / eq.

[0021] As a preferred solution, the viscosity of the phenolic modified epoxy resin is 2000-3000 cps at 150°C.

[0022] As a preferred solution, the viscosity of the phenolic modified epoxy resin is 2000-2500 cps at 150°C.

[0023] As a preferred solution, the softening point of the phenolic modified epoxy resin is 90-100°C.

[0024] In this application, the compounding and addition of the above-mentioned composite epoxy resin composition can effectively improve the mechanical properties, bonding properties and low-temperature curing properties of the adhesive, and can also effectively ensure that it has good waterproof and aging corrosion resistance. The three types of epoxy resins added in this application can form a variety of forces between the components in the adhesive system through the active sites between each other, and can form complex entanglements between multiple segments through the above-mentioned forces, which greatly improves the tightness between the molecular segments during the curing process, thereby achieving a deep curing effect inside and accelerating the curing efficiency; secondly, the more dense three-dimensional entanglement network formed inside the system can greatly limit the free efficiency of free groups, molecules and water molecules inside the adhesive, thereby greatly reducing the contact frequency between them inside, and reducing the possibility of aggregation and reaction between them. rate, during long-term use and storage, it can effectively limit the internal chemical reactions and water penetration, thereby obtaining excellent waterproof, aging-resistant and certain corrosion-resistant effects; finally, the combination of epoxy resins with corresponding epoxy equivalent, molecular weight and bromine content can effectively give the adhesive certain flame retardancy and mechanical properties improvement effects through bromination flame retardancy and carrier effect, especially the selective addition of phenolic modified epoxy resin can effectively serve as a carrier in the system of modified particles, enhance the spreading effect of modified particles in the system, and further modify the waterproof, aging-resistant and corrosion-resistant properties.

[0025] As a preferred solution, the preparation method of the modified particles comprises the following steps: S1: adding sericite powder and silicon dioxide to a deionized water solution, adding a pH regulator to adjust the pH to 9.5-10, then adding isopropyl alcohol and tetraethyl orthosilicate, heating to 55-60°C, stirring at 40-60rpm for 1-2h, centrifuging and filtering the product after the reaction is completed, washing with ethanol 2-3 times and vacuum drying to obtain pretreated mixed particles; S2: in a sealed reactor, mixing the pretreated mixed particles with zinc nitrate and dimethylimidazole, adding them to the deionized water solution, then heating to 65-70°C, and then drying the mixture under reduced pressure. ℃, during which time glutaric anhydride and silane coupling agent are added, and the mixture is stirred at 60-80rpm for 1.5-2h, and then a mixed deionized water solution containing 2,5-dihydroxyterephthalic acid is added dropwise, and the dropping time is 40-50min; S3: after the dropping is completed, the reaction kettle is sealed, the pressure in the kettle is controlled to be 1.8-2.1MPa, the temperature is raised to 180-200℃, and the mixture is stirred at 100-120rpm for 18-24h. After the reaction is completed, the temperature is naturally lowered to 60-80℃, sodium hydroxide is added to adjust the pH to 7-7.5, the product is centrifuged and filtered, washed with ethanol 2-3 times and vacuum dried to obtain the product.

[0026] As a preferred solution, the average particle size of the sericite powder is 1 to 1.5 μm.

[0027] As a preferred solution, the average particle size of the silicon dioxide is 20 to 35 nm.

[0028] As a preferred solution, the mass ratio of the sericite powder, silicon dioxide, isopropyl alcohol and tetraethyl orthosilicate is (5-6): (0.8-1): (0.1-0.2): (0.3-0.4).

[0029] As a preferred solution, the pH regulator is a mixture of diethanolamine and ammonia water; the mass ratio of diethanolamine to ammonia water is (3-4): (1-1.5).

[0030] As a preferred solution, the mass ratio of the pretreated mixed particles, glutaric anhydride and silane coupling agent is (5-5.5): (1.5-2): (0.3-0.4).

[0031] As a preferred solution, the silane coupling agent is 3-aminopropyltriethoxysilane.

[0032] As a preferred solution, the mass ratio of the pretreated mixed particles, zinc nitrate, dimethylimidazole and 2,5-dihydroxyterephthalic acid is (5-5.5): (2-2.5): (0.6-0.8): (1-1.5).

[0033] The modified particles added in the application can effectively improve the mechanical, waterproof and aging corrosion resistance of epoxy adhesives. The modified particles can use sericite powder as the surface embedded basic particles, and through the adhesion of silica on the surface and the subsequent modification of the active groups on the silica surface, ultimately strengthen the coordination and hydrogen bonding strength for the subsequent synthetic framework particles, thereby ultimately forming modified sericite powder particles with a surface embedded particle structure. The particles can be used as an excellent carrier to achieve excellent spreading effects in the internal system of the adhesive through the good intermolecular connection between sericite powder and the specific resin added in this application, thereby achieving a gradient of modified sericite powder from the inside to the outside of the adhesive. The stacking effect can greatly improve the mechanical properties of epoxy adhesive through the active connection effect in the micropores of particles and the point-surface support effect of modified sericite powder itself; secondly, the stacking phenomenon can also greatly increase the resistance of water molecules to penetrate into the adhesive and the length of the penetration path, and can greatly reduce the surface attraction and capture effect of water molecules in the air through the rough surface of modified sericite powder, thereby greatly inhibiting the formation of surface hydration layer, which can effectively block the invasion of water molecules or corrosive chemical molecules with water liquid as carrier during long-term use.

[0034] As a preferred solution, the accelerator is at least one of 2-methylimidazole, 2-ethyl-4-methylimidazole, stannous trifluoromethanesulfonate, maleic anhydride, and dimethylcyclohexylamine.

[0035] As a preferred solution, the accelerator is a combination of 2-ethyl-4-methylimidazole and 2-methylimidazole.

[0036] As a preferred solution, the mass ratio of the 2-ethyl-4-methylimidazole to 2-methylimidazole is (3-4):(0.2-0.5).

[0037] As a preferred solution, the mass ratio of the 2-ethyl-4-methylimidazole to 2-methylimidazole is (3.4-3.6): (0.3-0.4).

[0038] As a preferred solution, the curing agent is at least one of ethylenediamine, diethylenetriamine, m-phenylenediamine, isophoronediamine, phthalic anhydride and tetrahydrophthalic anhydride.

[0039] As a preferred solution, the curing agent is isophoronediamine.

[0040] As a preferred solution, the toughening agent is at least one of liquid nitrile rubber, hydroxyl-terminated polybutadiene, polyamide wax, and polyether amide.

[0041] As a preferred solution, the toughening agent is liquid nitrile rubber.

[0042] As a preferred solution, the active diluent is at least one of cyclohexyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, nonylphenol glycidyl ether, dicyclopentadiene epoxy resin, and trimethylolpropane triglycidyl ether.

[0043] As a preferred solution, the active diluent is a combination of cyclohexyl glycidyl ether and trimethylolpropane triglycidyl ether.

[0044] As a preferred solution, the mass ratio of cyclohexyl glycidyl ether to trimethylolpropane triglycidyl ether is (3-4):(1-2).

[0045] As a preferred solution, the mass ratio of cyclohexyl glycidyl ether to trimethylolpropane triglycidyl ether is (3.4-3.8):(1.2-1.5).

[0046] As a preferred solution, the stabilizer is at least one of 2,6-di-tert-butyl-4-methylphenol, N,N'-di-sec-butyl-p-phenylenediamine, 2,2,6,6-tetramethyl-4-piperidinol and 2-hydroxy-4-n-octyloxybenzophenone.

[0047] As a preferred solution, the stabilizer is a combination of 2,6-di-tert-butyl-4-methylphenol and N,N'-di-sec-butyl-p-phenylenediamine.

[0048] As a preferred solution, the mass ratio of 2,6-di-tert-butyl-4-methylphenol to N,N'-di-sec-butyl-p-phenylenediamine is (5-8):(2-4).

[0049] As a preferred solution, the dispersant is a composition of dodecyl dimethyl betaine and lauryl alcohol polyoxyethylene ether.

[0050] As a preferred solution, the mass ratio of dodecyl dimethyl betaine to lauryl alcohol polyoxyethylene ether is (2-2.5):(3-4).

[0051] The second aspect of the present application provides a method for preparing the above-mentioned low-temperature fast-curing epoxy adhesive, which specifically includes the following steps: S1: mixing the epoxy resin composition at 110-120°C and stirring until it is evenly mixed, then adding the modified particles and continuing to stir until the filler is completely dispersed; S2: then adding the active diluent first, stirring and mixing at 60-80rpm, naturally cooling to 60-70°C and then adding the remaining raw materials, and finally adding the curing agent during this period, stirring at 60-80rpm for 1-2h; S3: after the stirring is completed, the product is vacuum-debubbled for 20-25min, and then the product is stored or used at low temperature.

[0052] The third aspect of the present application provides an application of the above-mentioned low-temperature fast-curing epoxy adhesive in electronic components, sealing components, packaging industry, and automobile manufacturing industry.

[0053] The beneficial effects of this application are:

[0054] 1. The low-temperature fast-curing epoxy adhesive provided in the present application not only has excellent adhesion and low-temperature curing effect, but also can maintain excellent waterproofness, mechanical properties, aging corrosion resistance and other properties on this basis, thereby meeting the diverse performance requirements of existing scientific and technological products for epoxy adhesives and having excellent application prospects.

[0055] 2. A low-temperature, fast-curing epoxy adhesive provided in the present application can form a variety of molecular forces in the adhesive system through the active sites between each other through the compounding and addition of a specific epoxy resin composition, and can form a complex entanglement phenomenon between multiple segments through the above-mentioned forces, greatly improving the tightness between the molecular segments during the curing process, thereby achieving a deep curing effect inside and accelerating the curing efficiency; secondly, the formed more dense three-dimensional entanglement network inside the system can greatly limit the free efficiency of free groups, molecules and water molecules inside the adhesive, thereby greatly reducing the contact frequency between them inside, and reducing the probability of aggregation and reaction between them. During long-term use and storage, it can effectively limit the chemical reactions between the inside and the penetration of water, thereby obtaining excellent waterproof, aging-resistant and certain corrosion-resistant effects.

[0056] 3. A low-temperature, fast-curing epoxy adhesive provided in the present application, the combination of epoxy resins with corresponding epoxy equivalent, molecular weight and bromine content can effectively give the adhesive certain flame retardancy and improvement of mechanical properties through bromination flame retardancy, carrier effect, etc., especially the selective addition of phenolic modified epoxy resin can effectively serve as a carrier in the system of modified particles, enhance the spreading effect of modified particles inside the system, and further modify the waterproof, aging and corrosion resistance and other properties.

[0057] 4. The present application provides a low-temperature fast-curing epoxy adhesive, in which the added modified particles form modified sericite powder particles with a surface embedded particle structure. The particles can achieve excellent spreading effect in the internal system of the adhesive as an excellent carrier through the good intermolecular connection between the sericite powder and the specific resin added in the present application, thereby achieving a trapezoidal stacking effect of the modified sericite powder from the inside to the outside of the adhesive, and then greatly improving the mechanical properties of the epoxy adhesive through the active connection in the particle micropores and the point-to-surface support of the modified sericite powder itself; secondly, the stacking phenomenon can also greatly increase the resistance to the penetration of water molecules in the adhesive and the length of the penetration path, and can greatly reduce the surface attraction and capture effect of water molecules in the air through the rough surface of the modified sericite powder, thereby greatly inhibiting the formation of a surface hydration layer, and can effectively block the invasion of water molecules or corrosive chemical molecules with water liquid as a carrier during long-term use. DETAILED DESCRIPTION

[0058] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0059] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0060] Example 1

[0061] Example 1 The first aspect provides a low-temperature fast-curing epoxy adhesive, in which the raw materials are, by mass: 78.8 parts of epoxy resin composition, 18.5 parts of modified particles, 4.2 parts of accelerator, 22.8 parts of curing agent, 14.6 parts of toughening agent, 22.5 parts of active diluent, 1.6 parts of stabilizer, and 8.8 parts of dispersant.

[0062] The epoxy resin composition is a composition of bisphenol A epoxy resin, brominated epoxy resin and phenolic modified epoxy resin, and the mass ratio of the three is 5.4:0.8:1.6.

[0063] The epoxy equivalent of bisphenol A epoxy resin is 224 g / eq, and the E-51 model product sold by Baling Petrochemical Co., Ltd. is purchased.

[0064] The number average molecular weight of the brominated epoxy resin is 1600 Da, the bromine content of the brominated epoxy resin is 48.8 wt %, and the softening point of the brominated epoxy resin is 103° C. The brominated epoxy resin is purchased from Jiangsu Xingsheng Chemical Industry Co., Ltd. and is a product of model EP-1600.

[0065] The phenolic modified epoxy resin has an epoxy equivalent of 556 g / eq, a viscosity of 2400 cps, a softening point of 150° C., and a DER642U product sold by Shandong Guohua Chemical Co., Ltd.

[0066] The preparation method of modified particles comprises the following steps, calculated by mass: S1: adding 5.5 parts of sericite powder and 0.85 parts of silicon dioxide to 160 parts of deionized water solution, adding a pH adjuster to adjust the pH to 9.8, then adding 0.2 parts of isopropanol and 0.32 parts of ethyl orthosilicate, heating to 60°C, stirring at 50rpm for 1.5h, after the reaction is completed, centrifuging and filtering the product, washing it twice with ethanol and vacuum drying it to obtain pretreated mixed particles; S2: in a sealed reactor, mixing 5.4 parts of the pretreated mixed particles with 2.2 parts of zinc nitrate and 0.75 parts of dimethylimidazole and adding them to 220 parts of deionized water. The solution was heated to 65-70°C, during which 1.8 parts of glutaric anhydride and 0.38 parts of 3-aminopropyltriethoxysilane were added and stirred at 80 rpm for 2 hours, and then a mixed deionized water solution containing 1.4 parts of 2,5-dihydroxyterephthalic acid (30 parts in total) was added dropwise, and the dropping time was 50 minutes; S3: After the dropwise addition was completed, the reactor was sealed, the pressure in the reactor was controlled to 2.1 MPa, the temperature was raised to 200°C, and the reaction was stirred at 100 rpm for 20 hours. After the reaction was completed, the temperature was naturally lowered to 65°C, sodium hydroxide was added to adjust the pH to 7.2, the product was centrifuged and filtered, washed with ethanol 3 times and vacuum dried to obtain the product.

[0067] The average particle size of sericite powder is 1.4 μm; the average particle size of silicon dioxide is 22 nm.

[0068] The pH regulator is a mixture of diethanolamine and ammonia water, and the mass ratio of diethanolamine to ammonia water is 3.5:1.5.

[0069] The accelerator is a composition of 2-ethyl-4-methylimidazole and 2-methylimidazole, and the mass ratio of the two is 3.5:0.3.

[0070] The curing agent is isophorone diamine; the toughening agent is liquid nitrile rubber, which is a LR810 model product purchased from Shanghai Saikede Company.

[0071] The active diluent is a composition of cyclohexyl glycidyl ether and trimethylolpropane triglycidyl ether, and the mass ratio of the two is 3.5:1.4.

[0072] The stabilizer is a composition of 2,6-di-tert-butyl-4-methylphenol and N,N'-di-sec-butyl-p-phenylenediamine, and the mass ratio of the two is 6.5:2.5.

[0073] The dispersant is a composition of dodecyl dimethyl betaine and lauryl alcohol polyoxyethylene ether, and the mass ratio of the two is 2.2:3.6. Dodecyl dimethyl betaine was purchased from Shandong Poly Chemical Co., Ltd. BS-12 model product; lauryl alcohol polyoxyethylene ether was purchased from Shandong Hongyunchang Chemical Technology Co., Ltd. MOA-9 model product sold.

[0074] The second aspect of the present embodiment provides a method for preparing the above-mentioned low-temperature fast-curing epoxy adhesive, which specifically includes the following steps: S1: Mix the epoxy resin composition at 120°C and stir until it is evenly mixed, then add the modified particles and continue stirring until the filler is completely dispersed; S2: Then add the active diluent first, stir and mix evenly at 80rpm, add the remaining raw materials after naturally cooling to 70°C, and finally add the curing agent during this period, stirring at 60rpm for 1.5h; S3: After the stirring is completed, the product is vacuum-debubbled for 20min, and then the product is stored or used at low temperature.

[0075] Example 2

[0076] Example 2 The first aspect provides a low-temperature fast-curing epoxy adhesive, in which the raw materials are, by mass: 86 parts of epoxy resin composition, 16.2 parts of modified particles, 3.8 parts of accelerator, 20.6 parts of curing agent, 13.5 parts of toughening agent, 22.5 parts of active diluent, 1.8 parts of stabilizer, and 7.2 parts of dispersant.

[0077] The epoxy resin composition is a composition of bisphenol A epoxy resin, brominated epoxy resin and phenolic modified epoxy resin, and the mass ratio of the three is 5:1.4:2.2.

[0078] The epoxy equivalent of bisphenol A epoxy resin is 224 g / eq, and the E-51 model product sold by Baling Petrochemical Co., Ltd. is purchased.

[0079] The number average molecular weight of the brominated epoxy resin is 1600 Da, the bromine content of the brominated epoxy resin is 48.8 wt %, and the softening point of the brominated epoxy resin is 103° C. The brominated epoxy resin is purchased from Jiangsu Xingsheng Chemical Industry Co., Ltd. and is a product of model EP-1600.

[0080] The phenolic modified epoxy resin has an epoxy equivalent of 556 g / eq, a viscosity of 2400 cps, a softening point of 150° C., and a DER642U product sold by Shandong Guohua Chemical Co., Ltd.

[0081] The preparation method of modified particles comprises the following steps, calculated by mass: S1: adding 5.5 parts of sericite powder and 0.85 parts of silicon dioxide to 160 parts of deionized water solution, adding a pH adjuster to adjust the pH to 9.8, then adding 0.2 parts of isopropanol and 0.32 parts of ethyl orthosilicate, heating to 60°C, stirring at 50rpm for 1.5h, after the reaction is completed, centrifuging and filtering the product, washing it twice with ethanol and vacuum drying it to obtain pretreated mixed particles; S2: in a sealed reactor, mixing 5.4 parts of the pretreated mixed particles with 2.2 parts of zinc nitrate and 0.75 parts of dimethylimidazole and adding them to 220 parts of deionized water. The solution was heated to 65-70°C, during which 1.8 parts of glutaric anhydride and 0.38 parts of 3-aminopropyltriethoxysilane were added and stirred at 80 rpm for 2 hours, and then a mixed deionized water solution containing 1.4 parts of 2,5-dihydroxyterephthalic acid (30 parts in total) was added dropwise, and the dropping time was 50 minutes; S3: After the dropwise addition was completed, the reactor was sealed, the pressure in the reactor was controlled to 2.1 MPa, the temperature was raised to 200°C, and the reaction was stirred at 100 rpm for 20 hours. After the reaction was completed, the temperature was naturally lowered to 65°C, sodium hydroxide was added to adjust the pH to 7.2, the product was centrifuged and filtered, washed with ethanol 3 times and vacuum dried to obtain the product.

[0082] The average particle size of sericite powder is 1.4 μm; the average particle size of silicon dioxide is 22 nm.

[0083] The pH regulator is a mixture of diethanolamine and ammonia water, and the mass ratio of diethanolamine to ammonia water is 3.5:1.5.

[0084] The accelerator is a composition of 2-ethyl-4-methylimidazole and 2-methylimidazole, and the mass ratio of the two is 3.5:0.3.

[0085] The curing agent is isophorone diamine; the toughening agent is liquid nitrile rubber, which is a LR810 model product purchased from Shanghai Saikede Company.

[0086] The active diluent is a composition of cyclohexyl glycidyl ether and trimethylolpropane triglycidyl ether, and the mass ratio of the two is 3.5:1.4.

[0087] The stabilizer is a composition of 2,6-di-tert-butyl-4-methylphenol and N,N'-di-sec-butyl-p-phenylenediamine, and the mass ratio of the two is 6.5:2.5.

[0088] The dispersant is a composition of dodecyl dimethyl betaine and lauryl alcohol polyoxyethylene ether, and the mass ratio of the two is 2.2:3.6. Dodecyl dimethyl betaine was purchased from Shandong Poly Chemical Co., Ltd. BS-12 model product; lauryl alcohol polyoxyethylene ether was purchased from Shandong Hongyunchang Chemical Technology Co., Ltd. MOA-9 model product sold.

[0089] The second aspect of the present embodiment provides a method for preparing the above-mentioned low-temperature fast-curing epoxy adhesive, which specifically includes the following steps: S1: Mix the epoxy resin composition at 120°C and stir until it is evenly mixed, then add the modified particles and continue stirring until the filler is completely dispersed; S2: Then add the active diluent first, stir and mix evenly at 80rpm, add the remaining raw materials after naturally cooling to 70°C, and finally add the curing agent during this period, stirring at 60rpm for 1.5h; S3: After the stirring is completed, the product is vacuum-debubbled for 20min, and then the product is stored or used at low temperature.

[0090] Comparative Example 1

[0091] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the low-temperature fast-curing epoxy adhesive, in parts by mass, has the following raw materials: 90 parts of epoxy resin composition, 8.5 parts of modified particles, 4.2 parts of accelerator, 22.8 parts of curing agent, 14.6 parts of toughening agent, 22.5 parts of active diluent, 1.6 parts of stabilizer, and 6.2 parts of dispersant.

[0092] Comparative Example 2

[0093] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the low-temperature fast-curing epoxy adhesive, in parts by mass, has the following raw materials: 62.5 parts of epoxy resin composition, 29.5 parts of modified particles, 4.2 parts of accelerator, 22.8 parts of curing agent, 14.6 parts of toughening agent, 22.5 parts of active diluent, 1.6 parts of stabilizer, and 6.5 parts of dispersant.

[0094] Comparative Example 3

[0095] The specific implementation of this comparative example is basically the same as that of Example 1, except that the epoxy resin composition is a composition of bisphenol A epoxy resin, brominated epoxy resin and phenolic modified epoxy resin, and the mass ratio of the three is 7:0.5:0.2.

[0096] Comparative Example 4

[0097] The specific implementation of this comparative example is basically the same as that of Example 1, except that the epoxy resin composition is a composition of bisphenol A epoxy resin, brominated epoxy resin and phenolic modified epoxy resin, and the mass ratio of the three is 3.5:2.5:2.5.

[0098] Comparative Example 5

[0099] The specific implementation of this comparative example is basically the same as that of Example 1, except that the epoxy equivalent of the phenolic modified epoxy resin is 175 g / eq, and the DOPO type phenolic modified epoxy resin product is purchased from Suzhou Senfida Chemical Co., Ltd.

[0100] Comparative Example 6

[0101] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified particles comprises the following steps, calculated by mass: S1: adding 5.5 parts of sericite powder and 0.35 parts of silicon dioxide to 160 parts of deionized water solution, adding a pH adjuster to adjust the pH to 9.8, then adding 0.05 parts of isopropanol and 0.11 parts of ethyl orthosilicate, heating to 60°C, stirring at 50rpm to keep the reaction warm for 1.5h, after the reaction is completed, centrifuging and filtering the product, washing with ethanol twice and vacuum drying to obtain pretreated mixed particles; S2: in a sealed reactor, mixing 5.4 parts of the pretreated mixed particles with 2.2 parts of zinc nitrate and 0.75 parts of dimethyl The imidazole mixture was added to 220 parts of deionized water solution, and then the temperature was raised to 65-70°C. During this period, 1.8 parts of glutaric anhydride and 0.38 parts of 3-aminopropyltriethoxysilane were added, and the mixture was stirred at 80rpm for 2h. Then, a mixed deionized water solution containing 1.4 parts of 2,5-dihydroxyterephthalic acid (30 parts in total) was added dropwise, and the dropping time was 50min; S3: After the dropwise addition was completed, the reactor was sealed, the pressure in the reactor was controlled to 2.1MPa, the temperature was raised to 200°C, and the mixture was stirred at 100rpm for 20h. After the reaction was completed, the temperature was naturally lowered to 65°C, sodium hydroxide was added to adjust the pH to 7.2, the product was centrifuged and filtered, washed with ethanol 3 times and vacuum dried to obtain the product.

[0102] Comparative Example 7

[0103] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified particles comprises the following steps, calculated by mass: S1: adding 5.5 parts of sericite powder and 0.85 parts of silicon dioxide to 160 parts of deionized water solution, adding a pH adjuster to adjust the pH to 9.8, then adding 0.2 parts of isopropanol and 0.32 parts of ethyl orthosilicate, heating to 60°C, stirring at 50rpm to keep the reaction warm for 1.5h, after the reaction is completed, centrifuging and filtering the product, washing with ethanol twice and vacuum drying to obtain pretreated mixed particles; S2: in a sealed reactor, mixing 7.5 parts of the pretreated mixed particles with 1.2 parts of zinc nitrate and 0.35 parts of dimethylamino The mixture of azoles is added to 220 parts of deionized water solution, and then the temperature is raised to 65-70°C. During this period, 1.1 parts of glutaric anhydride and 0.15 parts of 3-aminopropyltriethoxysilane are added, and the mixture is stirred at 80rpm for 2h. Then, a mixed deionized water solution containing 0.6 parts of 2,5-dihydroxyterephthalic acid (30 parts in total) is added dropwise, and the dropping time is 50min; S3: After the dropwise addition is completed, the reactor is sealed, the pressure in the reactor is controlled to 2.1MPa, the temperature is raised to 200°C, and the mixture is stirred at 100rpm for 20h. After the reaction is completed, the temperature is naturally lowered to 65°C, sodium hydroxide is added to adjust the pH to 7.2, the product is centrifuged and filtered, washed with ethanol 3 times and vacuum dried to obtain the product.

[0104] Comparative Example 8

[0105] The average particle size of sericite powder is 5.5 μm; the average particle size of silicon dioxide is 55 nm.

[0106] Performance Evaluation

[0107] 1. Low temperature curing effect: The epoxy adhesives prepared in the examples and comparative examples were subjected to low temperature curing tests, with a curing temperature of 60°C and a curing time of 3.5 h. During this period, the initial curing time of the epoxy adhesive and the room temperature shear strength after final curing (reference standard GB / T7124-2008) were recorded. The test values ​​were the average of 10 tests and recorded in Table 1.

[0108] 2. Adhesion test: The epoxy adhesives prepared in the examples and comparative examples were cured by the method of performance test 1, and the peel strength was tested according to the reference standard GB / T 7122-1996. The test values ​​were the average of 10 tests and recorded in Table 1.

[0109] 3. Corrosion resistance: The epoxy adhesives prepared in the embodiments and comparative examples were cured by the method of performance test 1 to obtain samples. The sample thickness was 0.2 mm, the test temperature was 45°C, the relative humidity was 95±3%, the test liquid was 5wt% NaCl, the test time was 200 h, 50 samples were tested in each group, and the qualified rate test results are recorded in Table 1.

[0110] 4. Waterproofness: The epoxy adhesives prepared in the examples and comparative examples were cured by the method of performance test 1 to obtain samples. The sample thickness was 0.2 mm. The surface water contact angle was tested by the sessile drop method with a drop size of 2 μL and a test time of 15 s. The test values ​​were averaged from 10 tests and recorded in Table 1.

[0111] 5. Aging resistance: The epoxy adhesives prepared in the examples and comparative examples were cured by the method of performance test 1 to obtain samples with a thickness of 0.2 mm. The coated samples were placed in a constant temperature and humidity chamber at 75±2°C and 75% humidity for 2 months. After 2 months, the samples were taken out and observed for cracks, bubbles, damage, and oxidation. If any, they were marked as unqualified, otherwise, they were qualified. 50 samples were tested in each group, and the qualified rate test results were recorded in Table 1.

[0112] Table 1 Performance test results

[0113]

[0114]

[0115] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 8 in terms of curing performance, mechanical properties, waterproof performance and aging corrosion resistance. This is mainly due to the combined effect of the epoxy resin combination, modified particles and other compounding technical solutions specified in the present application. Comparative examples 1 to 8 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A low temperature fast curing epoxy adhesive, characterized in that: The raw materials are as follows, by mass: 60-90 parts of epoxy resin composition, 15-25 parts of modified particles, 3-5 parts of accelerator, 20-30 parts of curing agent, 10-20 parts of toughening agent, 15-30 parts of active diluent, 1-2.5 parts of stabilizer, and 4-12 parts of dispersant; The epoxy resin composition is a composition of bisphenol A epoxy resin, brominated epoxy resin and phenolic modified epoxy resin; The mass ratio of the bisphenol A epoxy resin, the brominated epoxy resin and the phenolic modified epoxy resin is (4-6): (0.5-1.5): (1.5-2.5); The epoxy equivalent of the bisphenol A epoxy resin is 200 to 300 g / eq; The number average molecular weight of the brominated epoxy resin is 1500 to 3000 Da; The epoxy equivalent of the phenolic modified epoxy resin is 500 to 650 g / eq; the viscosity of the phenolic modified epoxy resin is 2000 to 3000 cps at 150° C.; the softening point of the phenolic modified epoxy resin is 90 to 100° C.; Preparation method of the modified particles The following steps are involved: S1: Add sericite powder and silicon dioxide to a deionized water solution, add a pH adjuster to adjust the pH to 9.5-10, then add isopropyl alcohol and tetraethyl orthosilicate, heat to 55-60°C, stir at 40-60rpm to keep warm for 1-2h, after the reaction is completed, centrifuge and filter the product, wash with ethanol 2-3 times and vacuum dry to obtain pretreated mixed particles; S2: In a sealed reactor, mix the pretreated mixed particles with zinc nitrate and dimethylimidazole and add them to a deionized water solution, then heat to 65-70°C, add glutaric anhydride and silane The coupling agent is stirred at 60-80 rpm for 1.5-2 hours, and then a mixed deionized water solution containing 2,5-dihydroxyterephthalic acid is added dropwise for 40-50 minutes; S3: After the addition is completed, the reaction kettle is sealed, the pressure in the kettle is controlled to be 1.8-2.1 MPa, the temperature is raised to 180-200°C, and the reaction is stirred at 100-120 rpm for 18-24 hours. After the reaction is completed, the temperature is naturally lowered to 60-80°C, sodium hydroxide is added to adjust the pH to 7-7.5, the product is centrifuged and filtered, washed with ethanol 2-3 times and vacuum dried to obtain; The average particle size of the sericite powder is 1 to 1.5 μm; the average particle size of the silicon dioxide is 20 to 35 nm; The mass ratio of the sericite powder, silicon dioxide, isopropyl alcohol and tetraethyl orthosilicate is (5-6): (0.8-1): (0.1-0.2): (0.3-0.4); The mass ratio of the pretreated mixed particles, glutaric anhydride and silane coupling agent is (5-5.5): (1.5-2): (0.3-0.4); The mass ratio of the pretreated mixed particles, zinc nitrate, dimethylimidazole and 2,5-dihydroxyterephthalic acid is (5-5.5): (2-2.5): (0.6-0.8): (1-1.5); The accelerator is at least one of 2-methylimidazole, 2-ethyl-4-methylimidazole, stannous trifluoromethanesulfonate, maleic anhydride, and dimethylcyclohexylamine; The curing agent is at least one of ethylenediamine, diethylenetriamine, m-phenylenediamine, isophoronediamine, phthalic anhydride and tetrahydrophthalic anhydride; The toughening agent is at least one of liquid nitrile rubber, hydroxyl-terminated polybutadiene, polyamide wax, and polyether amide; The active diluent is at least one of cyclohexyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, nonylphenol glycidyl ether, dicyclopentadiene epoxy resin, and trimethylolpropane triglycidyl ether.

2. The low temperature fast curing epoxy adhesive according to claim 1, characterized in that: The mass ratio of the modified particles to the dispersant in the epoxy resin composition is (70-85):(16-22):(6-10).

3. The low temperature fast curing epoxy adhesive according to claim 2, characterized in that: The mass ratio of the epoxy resin composition, the curing agent and the toughening agent is (70-85): (20-25): (12-18).

4. The low temperature fast curing epoxy adhesive according to claim 3, characterized in that: The active diluent is a composition of cyclohexyl glycidyl ether and trimethylolpropane triglycidyl ether; the mass ratio of cyclohexyl glycidyl ether to trimethylolpropane triglycidyl ether is (3-4):(1-2).

5. The low temperature fast curing epoxy adhesive according to claim 4, characterized in that: The stabilizer is at least one of 2,6-di-tert-butyl-4-methylphenol, N,N'-di-sec-butyl-p-phenylenediamine, 2,2,6,6-tetramethyl-4-piperidinol and 2-hydroxy-4-n-octyloxybenzophenone.

6. The low temperature fast curing epoxy adhesive according to claim 5, characterized in that: The stabilizer is a composition of 2,6-di-tert-butyl-4-methylphenol and N,N'-di-sec-butyl-p-phenylenediamine; the mass ratio of the 2,6-di-tert-butyl-4-methylphenol and N,N'-di-sec-butyl-p-phenylenediamine is (5-8):(2-4).

7. The low temperature fast curing epoxy adhesive according to claim 6, characterized in that: The dispersant is a composition of dodecyl dimethyl betaine and lauryl alcohol polyoxyethylene ether; the mass ratio of the dodecyl dimethyl betaine to lauryl alcohol polyoxyethylene ether is (2-2.5): (3-4).

8. The low temperature fast curing epoxy adhesive according to claim 7, characterized in that: The bromine content of the brominated epoxy resin is 45-55wt%; the softening point of the brominated epoxy resin is 95-115°C.

9. A method for preparing a low-temperature fast-curing epoxy adhesive according to any one of claims 1 to 8, characterized in that: The specific steps include: S1: Mix the epoxy resin composition at 110-120° C. and stir until it is uniformly mixed, then add the modified particles and continue stirring until the filler is completely dispersed; S2: Then add the active diluent first, stir and mix at 60-80 rpm until it is uniformly mixed, naturally cool to 60-70° C. and then add the remaining raw materials, and finally add the curing agent during this period, and stir at 60-80 rpm for 1-2 hours; S3: After the stirring is completed, the product is vacuum-debubbled for 20-25 minutes, and then the product is stored or used at low temperature.

10. Use of the low-temperature fast-curing epoxy adhesive according to any one of claims 1 to 8 in electronic components, sealing components, packaging industry, and automobile manufacturing industry.

Citation Information

Cited By

  • High-strength yellowing-resistant plastic based on modified polypropylene and preparation method of high-strength yellowing-resistant plastic

    CN120484424A

  • High-strength yellowing-resistant plastic based on modified polypropylene and method for producing same

    CN120484424B